The mechanism of action of the controversial drug; aducanumab and the story behind its speedy approval - Zainab, Anika (Journal of the Pakistan Medical Association, 2022)
Dear Editor, Alzheimer’s disease is a neurodegenerative disease and is denoted by memory loss and cognitive deterioration. It gives rise to the two pathologic hallmarks: the neurofibrillary tangles and amyloid plaques. 1-2